1978
DOI: 10.1901/jeab.1978.30-239
|View full text |Cite
|
Sign up to set email alerts
|

Multiple Schedule Component Duration: A Re‐analysis of Shimp and Wheatley (1971) and Todorov (1972)

Abstract: The tendency for relative response rate to approach matching as multiple schedule component duration decreases has been interpreted as confirming a prediction of Herrnstein's multiple schedule equation. However, the equation predicts that absolute response rate will decrease in both multiple schedule components as component duration decreases. The absolute response-rate data of two studies of component duration do not support this prediction; absolute rate either increased or remained relatively constant.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
5
3

Year Published

1979
1979
2014
2014

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 10 publications
(8 citation statements)
references
References 7 publications
(5 reference statements)
0
5
3
Order By: Relevance
“…Additionally, several studies show that the modification of Equation 2, which Herrnstein (1970) proposed for multiple schedules, is also incorrect. Contrary to what Herrnstein's theory predicts, Edmon (1978) did not find an increase in the rates of responding as the components of the multiple schedule got longer. Several studies nave also shown that Herrnstein's theory makes incorrect predictions about the relation between simple and multiple-schedule responding (see McSweeney, 1980).…”
Section: Discussioncontrasting
confidence: 99%
“…Additionally, several studies show that the modification of Equation 2, which Herrnstein (1970) proposed for multiple schedules, is also incorrect. Contrary to what Herrnstein's theory predicts, Edmon (1978) did not find an increase in the rates of responding as the components of the multiple schedule got longer. Several studies nave also shown that Herrnstein's theory makes incorrect predictions about the relation between simple and multiple-schedule responding (see McSweeney, 1980).…”
Section: Discussioncontrasting
confidence: 99%
“…But there is one exception to this conclusion: the relation between component response rates and the alternation ratio requirement found in Experiment 1 and replicated in Experiment 2. This result has not been found in conventional multiple-schedule performance when component duration is varied (Charman & Davison, 1982;Edmon, 1978). We can offer no explanation for this difference.…”
Section: Resultscontrasting
confidence: 54%
“…In spite of its ability to account for a variety of different findings, Equation 9 also makes several incorrect predictions, as noted by several investigators (deVilliers, 1977;Edmon, 1978;McSweeney, 1980;McSweeney & Dericco, 1976;Spealman & Gollub, 1974 One problem that remains even with Equation 10 is the effect of absolute rate of reinforcement on the magnitude of contrast. As noted by Spealman and Gollub (1974) and McLean and White (in press),Equation 9 predicts that contrast should be greater the higher the rate of reinforcement, and this is true for Equation 10 as well.…”
Section: The Relationship Between Contrastmentioning
confidence: 99%